IJTIHAD: MAKNA DAN RELASINYA DENGAN SYARI’AH, FIQIH, DAN USHUL FIQIH - Supriyanto, Agus (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2010)
This article explains about ijtihad and its relation to shari?ah (Islamic law), fiqh (Islamic jurisprudence) and ushul fiqh (methodology of Islamic jurisprudence). Ijtihad ??????) ,) derives from jahada (struggle). Ijtihad is a technical term of Islamic law that describes the process of making a legal decision by independent interpretation of the legal sources (shari?ah), the Qur'an and the Sunnah. In ushul fiqh, these qualifications of mujtahid can be summed up as (i) an understanding of the objectives of the sharia and (ii) a knowledge of its sources and methods of deduction. The "gates of ijtihad" were "closed" in the 10th century in Sunni fiqh, meaning that ijtihad is not practiced in Sunni Islam anymore. In modern application, conservative Muslims say that most Muslims do not have the training in legal sources to conduct ijtihad. They argue that this role was traditionally given to those who have studied for a number of years under a scholar. However, liberal movements within Islam generally argue that any Muslim can perform ijtihad, given that Islam has no generally accepted clerical hierarchy or bureaucratic organization. A number of revivalist